POTENTIAL OF SWAMP GAS AS A SUBSTITUTE FOR FOSSIL ENERGY IN THE FRAMEWORK OF ENVIRONMENTALLY CONSCIOUS ENERGY DIVERSIFICATION IN EAST JAVA PROVINCE - Nurkholis; Suyono Thamrin; Mohamad Sidik Boedoyo (RADJA PUBLIKA, 2025)
This research aims to determine the distribution pattern of gas-containing sediments in East Java. The potential for biogenic gas in East Java can be determined by creating a shallow reflection seismic profile. The research locations are Sumenep Regency and Gresik Regency. The shallow reflection seismic profile of Sumenep Regency shows that sequences A and B are penetrated by mud diapirs. New black clay was discovered in the Holocene–Pleistocene Pamekasan Formation. In Sumenep, the formation of biogenic gas and deposition of sediment as source rock and reservoir occurred over a short period of time so that gas production was insufficient. The biogenic gas content near the surface in black clay is low, so there is no potential for further exploration. The minimal potential for biogenic gas near the surface in the Sumenep Basin is caused by tectonic processes, stratigraphic conditions (estuary systems) and structures (small faults and mud diapirs) which influence the migration and accumulation pathways of biogenic gas. In Gresik Regency, the potential distribution of sediment containing biogenic gas can only be observed laterally and is very difficult to observe vertically. The gas deposits are estimated to be in the C order and are evenly distributed